PENGARUH LINGKUNGAN KERJA NON-FISIK, SHIFT KERJA DAN STRES KERJA TERHADAP KINERJA TENAGA KESEHATAN PADA RUMAH SAKIT UMUM PREMAGANA GIANYAR - Risma Pingken Risnani; Gusti Ayu Sugiati; Ade Ruly Sumartini (Warmadewa Management and Business Journal (WMBJ), 2025)
This study aims to determine the influence of the non-physical work environment, work shifts and work stress on the performance of health workers at the Premagana General Hospital, Gianyar. The population used in this study were all health workers at Premagana Gianyar General Hospital and by using a simple random sampling technique, the number of samples was determined as many as 107 respondents. The results of research and analysis using SPSS show that: (1) The non-physical work environment, work shifts and work stress simultaneously have a significant effect on the performance of health workers. (2) The non-physical work environment partially has a positive and significant effect on the performance of health workers. (3) Shift work partially has a positive and significant effect on the performance of health workers. (4) Work stress partially has a negative and significant effect on the performance of health workers at Premagana General Hospital.